Place of death and phenomenon of going home to die in Chinese adults: a prospective cohort study - Weng, L; Hu, Y; Sun, Z; Yang, L; Chen, Y; Du, H; Pang, Y; Chen, Z (Elsevier, 2021)
Background: China is embracing an ageing population without sustainable end-of-life care services. However, changes in place of death and trends of going home to die (GHTD) from the hospital remains unknown.